2015
DOI: 10.1177/009164711504300403
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Humility and Forgiveness of Religious Conflict

Abstract: Intellectual humility (IH) involves an accurate view of one's intellectual strengths and weaknesses as well as the ability to negotiate different ideas in an interpersonally respectful manner. The current study examined how IH and perceptions of IH affect responses to a religious conflict. Participants (N = 200) were undergraduate students who filled out online questionnaires about their experience of a religious conflict. Participants rated (a) their own IH toward the offender's religious beliefs and values, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 30 publications
3
34
1
17
Order By: Relevance
“…In such cases, the uncertainty and stress of a religious conflict appear less likely to result in motivations of avoidance and revenge. This reasoning is in accordance with the findings of previous studies that have demonstrated the effectiveness of cultural humility in reducing worldview defense and regulating stressful emotions (Hook et al, 2015; Rodriguez et al, 2017; Zhang et al, 2015). Therefore, the results of this study provide further support for applying the social buffering hypothesis of humility to the context of systemic religious offenses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In such cases, the uncertainty and stress of a religious conflict appear less likely to result in motivations of avoidance and revenge. This reasoning is in accordance with the findings of previous studies that have demonstrated the effectiveness of cultural humility in reducing worldview defense and regulating stressful emotions (Hook et al, 2015; Rodriguez et al, 2017; Zhang et al, 2015). Therefore, the results of this study provide further support for applying the social buffering hypothesis of humility to the context of systemic religious offenses.…”
Section: Discussionsupporting
confidence: 92%
“…Students received a small amount of course credit as compensation for participation. Data from this study have been used elsewhere (Zhang et al, 2015), and the primary analyses in the manuscripts are different. Specifically, Zhang and colleagues analyzed the relationship of cultural humility toward the offender in the religious disagreement and the rating of the offender’s humility in predicting forgiveness, whereas this analysis includes moral foundations and assesses cultural humility regarding different religious beliefs and values in general.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, most studies of specific IH have focused on the domain of religion (e.g., Hook et al, 2017;Hopkin, Hoyle, & Toner, 2014;Van Tongeren et al, 2016;Zhang et al, 2015Zhang et al, , 2016, with research in the political domain starting to catch up. Extant research on IH and politics has found that IH is relevant to political attitudes, having focused primarily on topics such as evaluations of political candidates who changed their stance on an issue (Leary et al, 2017), openness to new arguments about issues like gun control (Porter & Schumann, 2018), or the degree to which someone thinks his/her group should be dominant in society (Krumrei-Mancuso & Newman, 2019).…”
Section: Sociopolitical Intellectual Humility and Specific Political mentioning
confidence: 99%
“…Complicating this shifting cultural landscape, our society is sharply divided along religious lines (Haidt, 2012). Religious disagreements are common (Zhang et al, 2015), and these conflicts may be intensified when opposing parties view their own beliefs as morally superior and are unwilling to engage in discourse under a generous assumption that the opposing views may be equally valid. Along these lines, prior work has documented that both people who are highly politically/religiously conservative and highly politically/religiously liberal are likely to view their own beliefs as superior to other viewpoints and tend to hold prejudice towards people with whom they disagree (Morgan, Mullen, & Skitka, 2010; Toner et al, 2013; Brandt & Van Tongeren, 2017).…”
mentioning
confidence: 99%